2019
DOI: 10.3889/oamjms.2019.720
|View full text |Cite
|
Sign up to set email alerts
|

Management of Severe Acute Pancreatitis

Abstract: Acute pancreatitis is one of the most common causes of hospitalisation from gastrointestinal diseases. The causes of pancreatitis vary between countries. Acute pancreatitis is classified based on Revised Atlanta classification 2013 as mild, moderately severe and severe acute pancreatitis. Acute pancreatic severity can be stratified by scoring systems such as Ranson’s score, BISAP score, APACHE-II score, SOFA score. In severe acute pancreatitis, to diagnose, abdominal pain raised amylase or lipase, supported im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
0
19
0
2
Order By: Relevance
“…In the present study, we found that the changes in plasma mtDNA levels showed a statistical consistency with the APACHE II, SOFA, and Ranson scores. Previous studies have con rmed that the APACHE II and Ranson scores are useful tools to evaluate the severity and prognosis of SAP [23][24][25]. The calculated Pearson correlation coe cients showed that that the mtDNA level correlated positively with the APACHE II, SOFA, and Ranson scores, suggesting that the mtDNA concentration might represent a new marker to evaluate SAP.…”
Section: Discussionmentioning
confidence: 82%
“…In the present study, we found that the changes in plasma mtDNA levels showed a statistical consistency with the APACHE II, SOFA, and Ranson scores. Previous studies have con rmed that the APACHE II and Ranson scores are useful tools to evaluate the severity and prognosis of SAP [23][24][25]. The calculated Pearson correlation coe cients showed that that the mtDNA level correlated positively with the APACHE II, SOFA, and Ranson scores, suggesting that the mtDNA concentration might represent a new marker to evaluate SAP.…”
Section: Discussionmentioning
confidence: 82%
“…Inhibition of exocrine the pancreatic secretion with octreotide which is somatostatin or its synthetic analogue, has been extensively studied. Although many studies have reported the effect of exocrine secretion inhibition on the course of the disease (11,22,23), it has also been reported that it reduces complications in elective surgery (24) and positively affects (25). In consequence, the place of medical treatment in acute pancreatitis treatment is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…The low level of user accuracy and producer accuracy could be due to difficulty of position matching between imagery and field data such as image position shift with GPS causing deplacement of observed object location [30]. In addition, the number of sample variations in the field also affects the results of accuracy [4].…”
Section: Table 4 Accuracy Assesment Based On Landsat 8 Satellite Imamentioning
confidence: 99%